2017
DOI: 10.1017/s095026881700036x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellain the pork production chain and its impact on human health in the European Union

Abstract: Salmonella spp. comprise the second most common food-borne pathogens in the European Union (EU). The role of pigs as carriers of Salmonella has been intensively studied both on farm and at slaughter. Salmonella infection in pigs may cause fever, diarrhoea, prostration and mortality. However, most infected pigs remain healthy carriers, and those infected at the end of the fattening period could pose a threat to human health. Contamination of pig carcasses can occur on the slaughter line, and it is linked to cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
142
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 97 publications
(210 reference statements)
10
142
2
2
Order By: Relevance
“…It was also observed that pork samples from retail markets possessed a significantly higher prevalence of Salmonella than those from wholesale markets, indicating that the environment may also be an important factor leading to Salmonella contamination. This is supported by the previous study that Salmonella in the environment can cause the contamination of pork (Bonardi, ). It is also possible that the difference in the prevalence of Salmonella between pork samples from retail and wholesale markets was attributed to the different origin of pig farms or slaughterhouses.…”
Section: Discussionsupporting
confidence: 86%
“…It was also observed that pork samples from retail markets possessed a significantly higher prevalence of Salmonella than those from wholesale markets, indicating that the environment may also be an important factor leading to Salmonella contamination. This is supported by the previous study that Salmonella in the environment can cause the contamination of pork (Bonardi, ). It is also possible that the difference in the prevalence of Salmonella between pork samples from retail and wholesale markets was attributed to the different origin of pig farms or slaughterhouses.…”
Section: Discussionsupporting
confidence: 86%
“…However, even under anaerobic conditions, the effect of the silCBA deletion on the MIC for copper was not comparable to the absence of SGI-4 in U288, DT104 and DT204 isolates which had a MIC that was below 5 mg/ml copper sulphate. Copper resistance at a similar level to these strains 9 was only observed in monophasic S. Typhimurium ST34 strain SO4698-09 when both silCBA and pcoABDE were deleted.…”
Section: Sgi-4 Confers Enhanced Resistance To Coppermentioning
confidence: 64%
“…Typhimurium DT104 emerged around 1990, becoming a globally pandemic clone that affects numerous domesticated and wild animal species (5). In 2007 a monophasic S. Typhimurium (S. 4, [5],12:i-) variant emerged in European pig populations and spread globally; monophasic S. Typhimurium is multi-locus sequence type 34 (ST34) (hereafter referred to as monophasic S. Typhimurium ST34), and predominantly phage type DT193 or DT120 (6)(7)(8)(9)(10)(11)(12). The mechanisms for succession in S. Typhimurium variants in Europe are not known, but selection by commonly-used antibiotics is unlikely since variants share similar AMR profiles (3): ACSSuT (ampicillin, chloramphenicol, streptomycin, sulphonamide, tetracycline) for S. Typhimurium DT104 and ASSuT for monophasic S. Typhimurium ST34.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella serovars in pork. Pigs are one of the most common sources of Salmonella infections in humans (38)(39)(40), and in some countries it is indicated as the most important source of salmonellosis, as in a great part of Europe and the United States (19,40). This is because these animals are frequently asymptomatic carriers and disseminators of this pathogen throughout the production chain.…”
Section: Discussionmentioning
confidence: 99%